2017
DOI: 10.3390/w9030156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climate Change on Hydrology, Sediment and Nutrient Losses in Two Lowland Catchments in Poland

Abstract: Future climate change is projected to have significant impact on water resources availability and quality in many parts of the world. The objective of this paper is to assess the effect of projected climate change on water quantity and quality in two lowland catchments (the Upper Narew and the Barycz) in Poland in two future periods (near future: 2021-2050, and far future: 2071-2100). The hydrological model SWAT was driven by climate forcing data from an ensemble of nine bias-corrected General Circulation Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…Changes in both precipitation and temperature together result in an estimated increase in streamflow in the Eno River by, on average, 14.1% and 12.5%, respectively, for the A2 and B1 scenarios. This result is consistent with another study for two lowland catchments (Upper Narew and Barycz) in Poland with similar characteristics to the study watershed that also found water yield would increase due to projected temperature and precipitation changes [19].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Changes in both precipitation and temperature together result in an estimated increase in streamflow in the Eno River by, on average, 14.1% and 12.5%, respectively, for the A2 and B1 scenarios. This result is consistent with another study for two lowland catchments (Upper Narew and Barycz) in Poland with similar characteristics to the study watershed that also found water yield would increase due to projected temperature and precipitation changes [19].…”
Section: Discussionsupporting
confidence: 93%
“…These GCM outputs are used to drive a calibrated SWAT model to simulate streamflow and inorganic nitrogen export. This study contributes to the growing research of climate change impacts in watershed hydrologic systems and water quality, specifically, on nitrogen export from watersheds with similar characteristics to the study watershed [18][19][20][21][22][23]. This study also contributes a methodology leveraging spatially-explicit data and analyses that can be applied to other critical and impaired watersheds across the world to better understand, from a mechanistic perspective, the specific relationship between changes in climate and nitrogen export for that watershed.…”
Section: Introductionmentioning
confidence: 99%
“…17-Marcinkowski et al [39] studied the effect of climate change on the hydrology and water quality in Poland. They predicted an increase in TN losses.…”
Section: Appendix Amentioning
confidence: 99%
“…Marcinkowski et al [41], by means of a hydrological model and nine General Circulation Model-Regional Climate Model (GCM-RCM) runs, evaluated pure effect of climate on water resources for the Upper Narew catchment for the 2020-2050 time horizon. They postulated that the median of projected changes in water yield, i.e., the portion of precipitation that reaches the stream, indicate an average annual increase of 9%.…”
Section: Hydrological Aspectsmentioning
confidence: 99%